Optimization of Pady Farming SRI Method (System of Rice Intensification) in Ngombol Purworejo - Istiko Agus Wicaksono; Dyah Panuntun Utami; Isna Windani; Erny Erny (AGROLAND The Agricultural Sciences Journal (e-Journal), 2015)
This study is aimed to determine: 1) The income level of rice farming using SRI method in Ngombol, Purworejo, 2) The allocation of optimal resources of rice farming SRI method in Ngombol, Purworejo, and 3) the effect of changing in input and output prices to optimal resource allocation. The method used is descriptive analysis method with 20 farmers as samples/respondents and implementing interview method using questionnaires. The study was conducted in the village names Ringgit, Ngombol, Purworejo. Study sites was selected by purposive sampling considering that Ngombol is the district with the highest rice production in Purworejo and Ringgit has been long time using SRI method, since 2003. This study were applying: 1) Analysis of the actual farm income, 2) QRP (Risk Quadratic Programming) Model Analysis, and 3) Sensitivity Analysis. The analysis showed that the average production of paddy SRI system A is greater than system B, but for the average cost of system B is higher but for the income system B is smaller than A. This illustrates that SRI paddy farming systems A more advantageous compared to systems B; Optimization analysis results indicate that from the average of the actual land area of 1.81 ha of activity that appears on the optimal cropping pattern farming area system A 1.27 ha and system B at 0.54 ha. Meanwhile, the system A selected as optimal farming pattern with the highest optimal cropping patterns, The results of the optimization analysis also showed that the land and labor resources are still abundant or excessive, where as capital resources are limited. The results of the sensitivity analysis shows that increase and decrease in input prices and output prices both partially and simultaneously for 5-15% do not affect the optimal allocation of resources, but only affects the risk of SRI paddy farming. The increase of input prices is the higher risk faced by rice farmers SRI and other wise higher selling price of output become smaller risk faced by farmers.